Maternal gut microbiota–psychotropic drug interactions and their impact on offspring neurodevelopment - Ashlee M. Craig; Kelly J. Clemens; Sarah-Jane Leigh (Clinical Science, 2026)
Abstract Pregnancy is associated with a unique and dynamic gut microbiota profile that supports fetal growth and neurodevelopment. Psychotropic drug–gut microbiota interactions are documented in the general population, yet less well described in pregnant women. Research has independently linked both perinatal psychotropic exposure and alterations to the maternal gut microbiome with potential changes to offspring neurodevelopment; therefore, it is plausible that similar interactions occur during pregnancy where they may influence maternal-fetal signaling pathways relevant to brain development. The aim of the present review is to explore the potential for interactions between perinatal psychotropic exposure and the maternal gut microbiota to shape long-term offspring neurodevelopment and psychiatric outcomes. By focusing on antidepressants, opioids/analgesics, and psychostimulants, potential mechanistic insights and gaps in the literature are highlighted to inform future research directions and therapeutic interventions. Collectively, the present review proposes the maternal gut microbiota as a previously underexplored yet significant modulator of neurodevelopment in the context of psychotropic drug exposure.